PENERAPAN FONETIK AKUSTIK DAN TEORI GRICE PADA REKAMAN PENYADAPAN TELEPON SEBAGAI ALAT BUKTI HUKUM: KAJIAN LINGUISTIK FORENSIK TERHADAP PERCAKAPAN ANTARA ARTALYTA SURYANI DENGAN JAKSA URIP TRI GUNAWAN - Hartini, Lilis (Sekolah Tinggi Hukum Bandung, 2010)
Forensic linguistics is a field of applied linguistics that involves the relationship between language, law, and crime. Practices law in this study as one solution in uncovering a legal case. This study is related to the study of transcript of telephone wiretap recordings to reveal how the subject of public law to lie. The method used is a qualitative descriptive method, a method that describes a conversation conducted Artalyta Suryani when his cell phone tapped the prosecution, viewed from the perspective of the principles of cooperation Grice. In descriptive research was conducted solely based on the facts presented or the phenomenon that is the emperis done by native speakers, whereas a qualitative approach that is pragmatic approach that bases itself on the reaction or response according to the conversational partner. The study results in a bribery case that was tapped by mobile phone is terdaspat deceit committed by the defendant.Â Pendingnya is they have to talk in riddles and use sign language.Keywords: Wiretapping - Forensic Linguistics - Law of Evidence